The Real Connections, Meaningful Algebra: Developing an Algebra Assesment Instrument Based on Construct Centered Design - Sahidi Sahidi; Usman Mulbar; Alimudin Tampa (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The low mathematical connection ability of junior high school students, particularly in algebra, remains a fundamental problem unsystematically addressed in Indonesian assessment practice. This study aims to develop a contextual-based algebraic connection instrument using the Construct Centered Design (CCD) approach that is valid, practical, and effective for ninth-grade junior high school students. A Research and Development (R&D) method was employed with a four-phase CCD design: (1) construct definition, (2) evidence design, (3) task design, and (4) evaluation. The instrument was piloted with 34 ninth-grade students at SMP Negeri 1 Kabupaten Sorong in the 2024/2025 academic year. Results indicate: (1) instrument validity reached 88.3% (very valid); (2) teacher practicality 85.0% and student practicality 82.6% (both very practical); (3) classical completeness 79.4% (effective). Student response analysis showed that the CCD based instrument can stratify students' connection profiles across three dimensions: inter-concept connections, cross-disciplinary connections, and contextual connections. The implications affirm the urgency of integrating construct-based approaches in developing mathematics assessment instruments to support Merdeka Curriculum implementation.